Excellence and Agile Management (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the importance of agility in the working environment?  Purpose: The purpose is to demonstrate the benefits of agile management when introduced into the operation of the organisation.Method: We did the article based on a review of foreign and domestic literature. We reviewed the professional literature on agility and the EFQM model.Results: We will find that there are differences between agile management and organizational culture in organizations that operate with an agile business approach from those that don’t. Effective communication and interaction skills, which are unique to the organization, are important for successful leaders of an agial organization. It is important that individuals in the organisation adopt a common vision, participate in a culture of trust and inclusion, while leaders promote creativity and experimentation.   Organisation: The research will show that agile organizations are achieving faster and more efficient adaptation to changes in the environment. Company: with an increased agile approach of working in organizations, thus creating an appropriate organisational culture has a positive impact on the satisfaction of all those involved in the process (employees, customers, suppliers,..) and consequently on adapting to the needs of the environment.  Originality: The research work shows the differences between agile rather than agile or traditional organisations. It is important to stress that changes in the working environment are constantly occurring, but that we can turn around with appropriate agile approaches in favor of introducing change.   Limitations/further research:It would be appropriate to present the survey in a particular organisation below. The restriction also represents a small number of articles and literature selected for comparison.
Keywords: business excellence; EFQM model; agile management; agility; agile organisation; working environment